Effects of Exercise on Mental Health of Elderly - Nafiseh Hekmati Pour; Hamid Hojjati (Guilan University of Medical Sciences, 2016)
Introduction: Elders due to retirement and reduction in income, more than other community members face financial difficulties and subsequently mental health problems such as depression and distress. Exercise can improve flexibility and mobility capabilities, cognitive function and improve mental compatibility and consistency of performance contributing to the quality of life of the aged people. Objective: This study aimed to determine the effect of exercise on mental health of elderly in Golestan Province. Method: In this Quasi experimental study with Salamon design, 48 elderly referring to daily centers in Golestan province in 2011 were selected by convenience sampling method and randomly divided to control and test groups. Then each group were divided to 12-member in two intervention and control groups one and two; the intervention and control groups 1 took pre-test while the intervention and control groups 2 did not take any tests. Intervention groups did the 15- 25 minutes exercise for four weeks during 16 sessions under the supervision of researcher. Exercise started with muscle warm ups for five minutes and then exercise movements were done and finally to cool down muscles, stretching the muscles were performed again. Finally, both demographic questionnaire and Mental Health Checklist were completed. Data were analyzed using descriptive and inferential statistics (ANOVA bilateral). Results: The average age of participants in this study was 76.71± 7.5 years, 32% of subjects were female and 68% male. 56% were married and 36% of them lost their spouse and 4% were single. Controlling the effect of the two-way ANOVA test showed significant differences between the intervention and control groups in self-esteem and life satisfaction scores (p= 0.004). And most level of mental health was observed in first intervention group with mean 21.57±2.89. Conclusion: Lack of physical activity (which is a phenomena of modern life) caused waste and lack of potential force that exists in each elderly to protect health and well being. Exercise improves flexibility and mobility capabilities, cognitive function and psychological adjustment, compatibility performance which contributes to the quality of life that is not possible to achieve with other therapies. Results showed regular exercise program promoted the mental health of elderly in intervention group. Therefore it is suggested to include regular exercise program suitable for elderly along with other care programs. It also seems the duration and type of activity in the elderly should be determined based on their ability and more fun activities such as walking and outdoor exercises in nursing homes to be included in their care plan.